STRATEGI MARKETING MIX OLAHAN SINGKONG (Manihot utilissima) DI PAKUDERJAN KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Karomah, Nuri Mubtadiyatul; Hartawaty, Dheny Arina (Fakultas Pertanian, Universitas Janabadra, 2023)
This study aims to find out about the right strategy to increase the marketing of processed cassava in PAKUDERJAN. This research was conducted at PAKUDERJAN, Job Village, Beji Village, Patuk District, Gunungkidul Regency. The data taken by researchers are primary data and secondary data. Primary data was obtained by observational data using a questionnaire with respondents in the study being PAKUDERJAN visitors or consumers consisting of 50 people. Secondary data obtained from literature studies sourced from journals, scientific books. Data collection was carried out during May 2023. The data analysis technique taken was the swot analysis technique, the swot matrix, the formulation of the IFAS matrix, the EFAS matrix and the IE matrix. The analysis phase is carried out by calculating the IFAS matrix consisting of strengths and weaknesses, the EFAS matrix consisting of opportunities and threats, the swot matrix to form a strategy in the marketing mix. Based on the research results, it is known that the total IFAS matrix is 3.23 and the total EFAS matrix is 3.09. Based on the results of the IFAS matrix and EFAS matrix values, the position of the IE matrix diagram is in quadrant 1, which means processed cassava food products are in phase (grow and build).Keywords: Cassava, PAKUDERJAN, Matriks EFAS, Matrik IFAS. INTISARIPenelitian ini bertujuan untuk mengetahui tentang strategi yang tepat untuk meningkatkan pemasaran olahan singkong di PAKUDERJAN. Penelitian ini dilakukan di PAKUDERJAN dusun Kerjan desa Beji kecamatan Patuk kabupaten Gunungkidul. Data yang diambil oleh peneliti yaitu data primer dan data sekunder. Data primer diperoleh dengan data observasi yang menggunakan alat bantu kuisioner dengan responden dalam penelitian adalah pengunjung PAKUDERJAN atau konsumen yang terdiri dari 50 orang. Data sekunder diperoleh dari studi Literatur yang bersumber dari jurnal,buku ilmiah. Pengambilan data dilakukan selama 1 bulan pada bulan Mei 2023. Teknik analisis data yang diambil adalah teknik analisis swot,matrik swot perumusan matriks IFAS, matriks EFAS dan matriks IE. Tahapan analisis dilakukan dengan langkah-langkah menghitung matrik IFAS yang terdiri dari kekuatan dan kelemahan, matrik EFAS yang terdiri dari peluang dan ancaman,matriks swot untuk membentuk strategi dalam bauran pemasaran. Bedasarkan hasil penelitian, diketahui total matriks IFAS adalah 3,23 dan total matriks EFAS adalah 3,09. Berdasarkan hasil nilai matriks IFAS dan matrik EFAS maka posisi diagram matriks IE berada di posisi sel 1 yang artinya produk makanan olahan singkong dalam fase (grow and build) tumbuh dan membangun.Kata kunci : Singkong, PAKUDERJAN, Matriks EFAS, Matrik IFAS.